2014
DOI: 10.4103/2277-9175.145729
|View full text |Cite
|
Sign up to set email alerts
|

Effects of biosurfactant produced by Lactobacillus casei on gtfB, gtfC, and ftf gene expression level in S. mutans by real-time RT-PCR

Abstract: Background:The Streptococci are the pioneer strains in plaque formation and Streptococcus mutans are the main etiological agent of dental plaque and caries. In general, biofilm formation is a step-wise process, which begins by adhesion of planktonic cells to the surfaces. Evidences show that expression of glucosyltransferase B and C (gtfB and gtfC) and fructosyltransferase (ftf) genes play critical role in initial adhesion of S. mutans to the tooth surface which results in formation of dental plaques and conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 45 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…Other researchers also showed that the application of biosurfactants derived from Lactobacillus casei and Lactobacillus rutteri caused considerable downregulation of the gtf B , gtf C , and ftf genes expression. [3738]…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers also showed that the application of biosurfactants derived from Lactobacillus casei and Lactobacillus rutteri caused considerable downregulation of the gtf B , gtf C , and ftf genes expression. [3738]…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that the anti-biofilm behavior of both excreted and cell-bound Lactobacillus BS can be ascribed to the downregulation of Gtfs genes, mainly gtfB and gtfC , as previously described for living probiotic cells ( 59 61 ). In addition, the expression of ftf , a proadhesive gene encoding for S. mutans fructosyltransferase, resulted significantly reduced in the presence of BS produced by L. acidophilus DSM20079 ( 59 ), L. casei ATCC39392 ( 60 ), and L. rhamnosus ATCC7469 ( 61 ).…”
Section: Beyond Probiotics: Lactobacillus Derivativesmentioning
confidence: 99%
“…As a result, it reduces the S. mutans attachment and biofilm formation. There are also other studies that demonstrate the ability of probiotic strains to down regulate gtf genes in S. mutans [ 31 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%